2011
DOI: 10.1097/mao.0b013e31822e5b27
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Cap Occlusion Technique for Dehiscent Superior Semicircular Canals

Abstract: The cartilage cap occlusion technique of dehiscent superior semicircular canals via a transmastoid and tegmen mini-craniotomy approach is a good option for managing symptomatic patients with a dehiscent superior semicircular canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…The success rates for the transmastoid approach were assessed in six studies. Of the six studies, three involved plugging, one involved a combination of plugging and resurfacing, and two involved resurfacing alone [i.e., “cartilage cap occlusion” (15)]. Reinforcement of the round window through the ear canal was assessed in one study.…”
Section: Resultsmentioning
confidence: 99%
“…The success rates for the transmastoid approach were assessed in six studies. Of the six studies, three involved plugging, one involved a combination of plugging and resurfacing, and two involved resurfacing alone [i.e., “cartilage cap occlusion” (15)]. Reinforcement of the round window through the ear canal was assessed in one study.…”
Section: Resultsmentioning
confidence: 99%
“…Although bone dust has been reported to be efficacious for the repair of tegmen defects, it has always been used with another substance (i.e., carbonated calcium phosphate, cartilage, duragen, fascia, muscle, split cranial bone) [2][3][4][5][6][7][8][9]. In contrast, when bone dust has been used alone to repair critical size calvarial gaps it does not ossify clinically [10][11][12] or experimentally [16][17][18].…”
Section: Discussionmentioning
confidence: 98%
“…Regardless of the type of surgical approach and substance used, recurrence of the cerebrospinal fluid leak is uncommon as long as the tegmen is repaired with multiple layers of different materials [1]. One substance that has been used commonly to reconstruct holes in the tegmen is bone dust collected from a high speed burr during the initial mastoidectomy or craniotomy [2][3][4][5][6][7][8][9]. The autologous bone dust then is typically mixed with blood, and/or fibrin glue to form a paste, before it is used to fill the bony defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early feasibility studies on hearing preservation after canal plugging were observed by Parnes and McClure among guinea pigs [Parnes and McClure, 1985]. Among human-beings, the preservation of hearing thresholds has been observed in patients undergoing canal plugging of the posterior canal through the transmastoid approach and the superior canal by the middle cranial fossa approach [Agrawal and Parnes, 2001;Banakis Hartl and Cass, 2018;Beyea et al, 2012;Lundy et al, 2011;Niesten et al, 2013;Powell et al, 2016;Van Haesendonck et al, 2016;Yamauchi et al, 2017] as well as the superior canal by middle cranial fossa approach [Ward et al, 2012]. Generally, surgery has a positive impact of the symptoms of SCDS.…”
Section: Introductionmentioning
confidence: 99%